Improving the Prevention of Shoulder Subluxation in Patients with Post-Stroke Hemiparesis - Kaisin, V.; Khramtsov, D.; Kozlova, H. (Journal of Education, Health and Sport, 2026)
Background: Shoulder subluxation is a common and clinically significant complication of post-stroke hemiparesis, particularly in the early recovery period, when muscle hypotonia and impaired motor control predominate. It is associated with increased risk of hemiplegic shoulder pain and reduced functional recovery, highlighting the need for effective preventive strategies. Objective: To improve prevention of shoulder subluxation in patients with post-stroke hemiparesis by evaluating the effectiveness of combining supportive interventions with Mulligan Mobilization with Movement (MWM) manual techniques. Methods: A prospective randomized controlled trial included 43 patients (45–80 years) in the early recovery period (7–90 days post-stroke). Participants were randomly assigned to a control group (n=21), receiving standard rehabilitation, or a main group (n=22), receiving additional MWM techniques. Outcomes were assessed at baseline and after 4–6 weeks using Fugl–Meyer Assessment for Upper Extremity (FMA-UE), Action Research Arm Test (ARAT), Visual Analog Scale (VAS), Modified Barthel Index (MBI), and acromiohumeral distance (AHD). Statistical analysis included Mann–Whitney U test and Spearman correlation (p<0.05). Results: Both groups improved; however, the main group demonstrated significantly greater gains in motor function (FMA-UE: 48 vs 41; p=0.003) and functional activity (ARAT: 38 vs 28; p=0.002), along with greater pain reduction (VAS: 1 vs 2; p=0.01) and improved joint stability (AHD: 9.8 mm vs 11.5 mm; p=0.004). Strong positive correlation was observed between FMA-UE and ARAT (ρ=0.71; p<0.001), while AHD and VAS negatively correlated with functional outcomes. Conclusions: The addition of Mulligan MWM techniques to standard rehabilitation significantly enhances motor recovery, reduces pain, and improves shoulder stability in post-stroke patients, supporting their inclusion in early rehabilitation protocols.